2015
DOI: 10.18011/bioeng2015v9n4p368-380
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Nível De Ruído, Itens De Segurança E Ergonomia Em Tratores Agrícolas

Abstract: RESUMOO ruído das máquinas agrícolas, com o passar do tempo, pode provocar problemas auditivos nos operadores. De acordo com as normas regulamentadoras do Ministério do Trabalho e Emprego (NR 15), a exposição diária máxima permitida, durante uma jornada de trabalho de 8 horas, é de 85 decibels (dB (A)). Baseado neste contexto, este trabalho teve como objetivo avaliar os níveis de ruído emitidos por 12 tratores agrícolas de diferentes modelos e potências, bem como avaliar a existência de itens de ergonomia e se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
8
0
3
Order By: Relevance
“…Studying some models of tractors, Gonçalves et al (2013) found that for an 8 h working day the noise levels of the tractors were above the level allowed by NR 15. Baesso et al (2015) evaluated 12 tractors of different models and concluded that tractors without a closed cabin had noise levels close to the operator's ear above the levels allowed by NR 15, being necessary the use of ear protectors. Studies performed by Rinaldi et al (2008), Alves et al (2011) and Nascimento et al (2013) also concluded that farm machinery noise levels were above tolerance limits, being needed to take measures to reduce or eliminate the risk which the workers were exposed in the agricultural operations.…”
Section: Resultsmentioning
confidence: 99%
“…Studying some models of tractors, Gonçalves et al (2013) found that for an 8 h working day the noise levels of the tractors were above the level allowed by NR 15. Baesso et al (2015) evaluated 12 tractors of different models and concluded that tractors without a closed cabin had noise levels close to the operator's ear above the levels allowed by NR 15, being necessary the use of ear protectors. Studies performed by Rinaldi et al (2008), Alves et al (2011) and Nascimento et al (2013) also concluded that farm machinery noise levels were above tolerance limits, being needed to take measures to reduce or eliminate the risk which the workers were exposed in the agricultural operations.…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Baesso et al [2], a maioria dos tratores agrícolas em operação no Brasil têm algum problema em relação à segurança e ergonomia do operador. Com a constatação de doenças ocupacionais dos operadores de máquinas agrícolas, temse buscado melhorias nesses postos de trabalho [3].…”
Section: ____________________________________________________________unclassified
“…Sendo assim, os operadores e auxiliares estariam sujeitos aos riscos de hipoacusia, quando trabalham sem proteção auricular. De acordo com Baesso et al [2], a maioria dos tratores agrícolas sem cabine apresentam um nível de ruído superior a 85 dB, sendo assim, obrigatório o uso de protetores auriculares ou a redução da jornada de trabalho diária.…”
Section: Metodologiaunclassified
“…Noise analysis has shown the need for all operators to wear the recommended hearing protector since, on average, all forestry equipment is close to the 80 dB(A) action limit set by NR-15 [17]. The source of the intense noise may be in the field, as there are several plots and forestry machines working in an integrated manner, so, at times, the noise of one can interfere with the other [18]. Allied to this, the results indicate some insulation failure of the machine cabs, which is a relevant problem.…”
Section: Occupational Noise Assessmentmentioning
confidence: 99%